Analisis Penetapan Harga Pokok Produksi dalam Menentukan Harga Jual di PT. Wonokoyo Jaya Kusuma - Asep Sulaeman, Wildan Maulana; Dali, Rahmat Mulyana; Rasiman, Rasiman (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The aim of this research is to calculate the production costs of a production of PT. Wonokoyo Jaya Kusuma, because production costs are one of the calculation tools in decision making, and to explain the determination of the selling price at PT. Wonokoyo Jaya Kusuma. This research is a type of qualitative descriptive research. To find out the cost and selling price of PT. Wonokoyo Jaya Kusuma, conducted by means of interviews, which were then analyzed qualitatively. Based on the results of research and data analysis, it can be concluded that there are several differences between production costs and selling prices at PT. Wonokoyo Jaya Kusuma with the author. The selling price of PT. Wonokoyo Jaya Kusuma follows the market price of Rp. 20,000 while according to the author's calculations using accounting theory that is equal to Rp. 22,300. PT. Wonokoyo Jaya Kusuma can follow the market price as long as the price is not higher than the cost of production because it will ensure that the company suffers a loss.